2014
DOI: 10.1002/jbm.a.35143
|View full text |Cite
|
Sign up to set email alerts
|

Use of a chondroitin sulfate bioadhesive to enhance integration of bioglass particles for repairing critical-size bone defects

Abstract: Replacement of autogenous or allograft bones by artificial graft materials represents a growing area of interest in current bone repair strategies. Bioactive ceramics in particulate form, such as Bioglass (BG) 45S5, stimulate bone mineralization comparable to autologous bone grafts, but have potential issues of particle migration and inflammation. The aim of this study was to employ a chondroitin sulfate- (CS-) based bioadhesive to improve integration of the bioglass (NovaBone Putty) to prevent particle migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Tissue particle hydrogels shared similar crosslinking chemistries with our previous protein based nonparticulate CS–bone marrow gels, but the large particle sizes ranging from nanoparticles up to several microns resulted in this study in an aggregate composite material. Despite these physical differences the rheological behavior of CS–ECM particle hydrogels was relatively similar to CS–bone marrow gels …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue particle hydrogels shared similar crosslinking chemistries with our previous protein based nonparticulate CS–bone marrow gels, but the large particle sizes ranging from nanoparticles up to several microns resulted in this study in an aggregate composite material. Despite these physical differences the rheological behavior of CS–ECM particle hydrogels was relatively similar to CS–bone marrow gels …”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, CS–NHS and HA–NHS molecules have been combined with synthetic and biological linker materials to form CS–composite hydrogels linked by either six arm PEG amine (PEG–(NH 2 ) 6 ), bone marrow, blood, or bioactive ceramic particles (90–710 μm) . Here, we hypothesize that the CS–NHS and HA–NHS was able to link to ECM particles via collagen and many other proteins with free amine groups on their surface.…”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory stage of development, hydrogels are being modified to include adhesive properties for an increased integration in the tissue [58][59][60] Review Abdel-Sayed & Pioletti charides with methacrylate and aldehyde groups to covalently link the cartilage proteins with the polyethylene glycols-based hydrogel they developed [58]. They have tested their material in chondral defects (3.2 mm diameter) in the femoropatellar groove of New Zealand white rabbits, and they have shown that with their multifunctional approach they can induce cartilage repair with a mechanical stability.…”
Section: Evolution Of Biomaterials Platforms Functionalization Of Thementioning
confidence: 99%
“…Bone tissue possesses the capability of self‐repair after injuries depending on the defect area, host immune response and systemic health conditions . In several cases, the use of titanium‐based implants is required to restore part of the damaged bone tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Bone tissue possesses the capability of self-repair after injuries depending on the defect area, host immune response and systemic health conditions. [1][2][3] In several cases, the use of titanium-based implants is required to restore part of the damaged bone tissue. [4][5][6][7] On the other hand, tissue engineering has focused on producing bone substitutes by using bioactive ceramics, polymers, and composites.…”
Section: Introductionmentioning
confidence: 99%